2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541317
|View full text |Cite
|
Sign up to set email alerts
|

The unbounded benefit of encoder cooperation for the k-user MAC

Abstract: Cooperation strategies allow communication devices to work together to improve network capacity. Consider a network consisting of a k-user multiple access channel (MAC) and a node that is connected to all k encoders via rate-limited bidirectional links, referred to as the "cooperation facilitator" (CF). Define the cooperation benefit as the sum-capacity gain resulting from the communication between the encoders and the CF and the cooperation rate as the total rate the CF shares with the encoders. This work dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Similarly, in [4], [7], an analog to Lemma 2 is shown for asymptotic blocklength. Specifically, it is shown that the existence of distributions p X1 p X2 ∈ P and p X1 X2 over X 1 × X 2 such that (a) the support of p X1 X2 is included in that of p X1 p X2 , and (b)…”
Section: A Comparison To Prior Workmentioning
confidence: 78%
See 4 more Smart Citations
“…Similarly, in [4], [7], an analog to Lemma 2 is shown for asymptotic blocklength. Specifically, it is shown that the existence of distributions p X1 p X2 ∈ P and p X1 X2 over X 1 × X 2 such that (a) the support of p X1 X2 is included in that of p X1 p X2 , and (b)…”
Section: A Comparison To Prior Workmentioning
confidence: 78%
“…In [4], an analog to Theorem 3 is proven for the asymptotic blocklength regime. Namely, in our notation, [4] proves that for any > 0 and δ > 0, if we set K = 2 Ω(n) then there exist n such that,…”
Section: A Comparison To Prior Workmentioning
confidence: 85%
See 3 more Smart Citations